Online inside and out: upper secondary students' expectations of a mental health interactive program in Sweden - Holmäng, Helena; Larsson, Margaretha; Knez, Rajna; Carlén, Kristina (Frontiers in Public Health, 2025)
BackgroundAdolescence represents a critical developmental stage with significant implications for long-term health and wellbeing. As this period increasingly takes place within digital environments, concerns regarding adolescent mental health have intensified. Students enrolled in the Introductory Programs (IM) in upper secondary school constitute a particularly vulnerable population, exhibiting heightened risks for mental health challenges and potential future social exclusion. These factors make IM students a key population for targeted mental health promotion efforts, yet little is known about how they perceive such initiatives or what they hope to gain from participation. Accordingly, this study aimed to describe the expectations of IM students regarding the implementation of On the Inside in relation to their mental health.MethodsThis study employed a qualitative design guided by reflexive thematic analysis. Data were collected through semi-structured individual and focus group interviews with 17 students enrolled in IM programs. The interviews were conducted at the outset of the mental health interactive program On the Inside.ResultsAnalysis yielded four themes: Establishing a balanced lifestyle as a foundation for growth; Finding focus and connection beyond the screen; Seeing yourself and others more clearly; and Building self-esteem through awareness and agency. These themes illustrate participants' perceptions of On the Inside as a valuable opportunity for personal reflection, emotional development, and intentional behavioral change aimed at enhancing mental wellbeing.ConclusionThe findings highlight students' aspirations for increased self-awareness and alignment between their inner experiences and external lives, including their emotional needs, personal values, and life goals. Moreover, the study underscores the relevance of fostering healthier digital habits among adolescents to support mental wellbeing and positive development. These insights may inform the development and implementation of future mental health interventions targeting vulnerable youth populations.